2003
DOI: 10.1097/01.brs.0000068243.63203.a8
|View full text |Cite
|
Sign up to set email alerts
|

Sitting with Adjustable Ischial and Back Supports: Biomechanical Changes

Abstract: Sitting with reduced ischial support and fitted backrest to the lower spine altered the contact area, reduced peak pressure under the ischia, reduced muscular activity, maintained total and segmental lumbar lordosis, rotated the sacrum forward, and increased lumbar intervertebral disc heights, which could potentially reduce low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
53
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(62 citation statements)
references
References 43 publications
7
53
1
1
Order By: Relevance
“…[10][11][12] Other studies have demonstrated the ability to change cutaneous tissue oxygenation by means of a dynamic cushion 5 and by means of a wheelchair in which the back part of the seat could be lowered to relieve the ischial tuberosities. 6 This study confirmed the ability of a seating device to create an alternating load on the seating surface of individuals with spinal cord disorders and, unlike the aforementioned studies, based its experimental protocol on the sitting behavior of healthy subjects. 8 Similar to previous studies, this study used the noninvasive measurement of cutaneous oxygenation.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…[10][11][12] Other studies have demonstrated the ability to change cutaneous tissue oxygenation by means of a dynamic cushion 5 and by means of a wheelchair in which the back part of the seat could be lowered to relieve the ischial tuberosities. 6 This study confirmed the ability of a seating device to create an alternating load on the seating surface of individuals with spinal cord disorders and, unlike the aforementioned studies, based its experimental protocol on the sitting behavior of healthy subjects. 8 Similar to previous studies, this study used the noninvasive measurement of cutaneous oxygenation.…”
Section: Discussionsupporting
confidence: 58%
“…Therefore, to reduce demands on nursing staff and increase the patient autonomy, seating devices have been developed that create dynamic, alternating seating patterns that mimic the reposition behavior as recommended by AHRQ. Both a dynamic cushion 5 and a dynamic seating device 6 have been studied as mechanisms to reduce tissue load. Positive effects of seating patterns with alternating loads were found on the skin oxygen tension of the buttock tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged lumbar flexion is also thought to elevate low back discomfort through increased loading of the passive tissues of the lumbar spine [29], tissues which are highly innervated with nociceptors [30,31,32]. The ability to maintain lumbar lordosis while minimizing peak pressures on the lumbar spine are important for decreasing low back discomfort [12,13]. Control of the anterior/posterior and vertical positions of the lumbar support likely allowed officers to maintain a more lordotic lumbar posture while minimizing the pressures produced by the lumbar support.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the use of a lumbar support system has been shown to aid in the maintenance of a person's natural lordotic lumbar curvature during sitting [10,11] which has been associated with reducing lower back discomfort [12,13]. The use of lumbar massage systems in automobile seats have also been shown to reduce lower back discomfort [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…[33,34] There were no significant that sitting for more than 3 hours daily could be a risk factor for LBP. [35,36] Regarding sitting, biomechanical research on risk factors has identified significant ergonomic predictors to be the trunk angle as well as time in this position [37] and twisted trunk posture. Our study has neither examined these factors nor has it been a biomechanical investigation.…”
Section: -Discussionmentioning
confidence: 99%